Dapagliflozin maintains glycaemic control while reducing weight and body fat mass over 2 years in patients with type 2 diabetes mellitus inadequately controlled on metformin. Issue 2 (29th August 2013) - Bolinder, J.; Ljunggren, Ö.; Johansson, L.; Wilding, J.; Langkilde, A. M.; Sjöström, C. D.; Sugg, J.; Parikh, S.
<x xml:space="preserve">Abstract</x> Aims Dapagliflozin, a highly selective inhibitor of sodium‐glucose cotransporter 2 (SGLT2), reduces hyperglycaemia and weight in patients with type 2 diabetes mellitus (T2DM) by increasing urinary glucose excretion. Long‐term glycaemic control, body composition and bone safety were evaluated in patients with T2DM after 102 weeks of dapagliflozin treatment. Methods This randomized, double‐blind, placebo‐controlled study (NCT00855166) enrolled patients with T2DM [mean: age 60.7 years; HbA1c 7.2%; body mass index (BMI) 31.9 kg/m2; body weight 91.5 kg] inadequately controlled on metformin. Patients (N = 182) were randomly assigned 1 : 1 to receive dapagliflozin 10 mg/day or placebo added to open‐label metformin for a 24‐week double‐blind treatment period followed by a 78‐week site‐ and patient‐blinded extension period. At week 102, changes from baseline in HbA1c, weight, waist circumference, total body fat mass as measured by dual‐energy X‐ray absorptiometry (DXA), serum markers of bone turnover, bone mineral density (BMD) as measured by DXA, and adverse events were evaluated. Results A total of 140 patients (76.9%) completed the study. Over 102 weeks, dapagliflozin‐treated patients showed reductions in HbA1c by −0.3%, weight by −4.54 kg, waist circumference by −5.0 cm and fat mass by −2.80 kg without increase in rate of hypoglycaemia. Compared with placebo, no meaningful changes from baseline in markers of bone turnover or BMD were identified over 102 weeks. One fracture occurred in each treatment group. The frequency of urinary tract infection (UTI) and genital infection was similar in both treatment groups. Conclusions Over 102 weeks, dapagliflozin improved glycaemic control, and reduced weight and fat mass, without affecting markers of bone turnover or BMD in patients with T2DM inadequately controlled on metformin.